Physiological and Proteomic Responses of Contrasting Alfalfa (Medicago sativa L.) Varieties to PEG-Induced Osmotic Stress - Zhang, Cuimei; Shi, Shangli (Frontiers in Plant Science, 2018)
Drought severely limits global plant distribution and agricultural production. Elucidating the physiological and molecular mechanisms governing alfalfa stress responses will contribute to the improvement of drought tolerance in leguminous crops. In this study, the physiological and proteomic responses of two alfalfa (Medicago sativa L.) varieties contrasting in drought tolerance, Longzhong (drought-tolerant) and Gannong No. 3 (drought-sensitive), were comparatively assayed when seedlings were exposed to -1.2 MPa polyethylene glycol (PEG-6000) treatments for 15 days. The results showed that the levels of proline, malondialdehyde (MDA), hydrogen peroxide (H2O2), hydroxyl free radical (OH•) and superoxide anion free radical (O2•-) in both varieties were significantly increased, while the root activity, the superoxide dismutase (SOD) and glutathione reductase (GR) activities, and the ratios of reduced/oxidized ascorbate (AsA/DHA) and reduced/oxidized glutathione (GSH/GSSG) were significantly decreased. The soluble protein and soluble sugar contents, the total antioxidant capability (T-AOC) and the activities of peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) first increased and then decreased with the increase in treatment days. Under osmotic stress, Longzhong exhibited lower levels of MDA, H2O2, OH• and O2•- but higher levels of SOD, CAT, APX, T-AOC and ratios of AsA/DHA and GSH/GSSG compared with Gannong No.3. Using isobaric tags for relative and absolute quantification (iTRAQ), 142 differentially accumulated proteins (DAPs) were identified from two alfalfa varieties, including 52 proteins (34 up-regulated and 18 down-regulated) in Longzhong, 71 proteins (28 up-regulated and 43 down-regulated) in Gannong No. 3, and 19 proteins (13 up-regulated and 6 down-regulated) shared by both varieties. Most of these DAPs were involved in stress and defense, protein metabolism, transmembrane transport, signal transduction, as well as cell wall and cytoskeleton metabolism. In conclusion, the stronger drought-tolerance of Longzhong was attributed to its higher osmotic adjustment capacity, greater ability to orchestrate its enzymatic and non-enzymatic antioxidant systems and thus avoid great oxidative damage in comparison to Gannong No. 3. Moreover, the involvement of other pathways, including carbohydrate metabolism, ROS detoxification, secondary metabolism, protein processing, ion and water transport, signal transduction, and cell wall adjustment, are important mechanisms for conferring drought tolerance in alfalfa.